Intergenerational ambivalences new perspectives on parent-child relations in later life - Pillemer, Karl A.; Lüscher, Kurt. (Amsterdam ; Boston : Elsevier/JAI, 2004)
This book is an in-depth, cutting-edge report on the intergenerational ambivalence perspective: an innovative framework for understanding parent-adult child relationships that has emerged from work in several disciplines such as sociology, psychology, history, and family therapy in the US and Europe over the past ten years. It is an excellent starting point for anyone interested in the ambivalent feelings experienced between adult children and their parents. With dramatic increases in the life span, many people now have adult relationships with their parents that last 30, 40, or even more years. These intergenerational bonds are perhaps the most stable and enduring ties people experience in our rapidly changing world. At the same time, social norms for how these relationships "should" be conducted have weakened, and many parents and adult children are struggling to understand their roles and responsibilities toward one another. Studying the nature and dynamics of intergenerational ties has now become a key task for social scientists, and a remarkably vigorous area for research. The perspective offered here draws on theory and research that highlight ambivalence as a key organizing concept for the study of intergenerational relations. Rather than focusing on consensus and support on one hand, or conflict on the other, this volume reveals parent-adult child relationships as a complex mix of positive and negative emotions, thoughts and attitudes. This volume's 13 chapters lay out the conceptual and methodological framework for this new perspective, and report on a number of empirical studies. The multidisciplinary group of leading researchers examines core dilemmas facing parents and adult children in the new millennium, the ambivalence such dilemmas create, and how people manage and cope with it.
Introduction: Ambivalence in Parent-Child Relations in Later Life / Karl Pillemer and Kurt Luscher -- Conceptualizing and Uncovering Intergenerational Ambivalence / Kurt Luscher -- Intergenerational Ambivalences in the Past - A Social-Historical Assessment / Andrejs Plakans -- Methodological Issues in Assessing Ambivalences in Intergenerational Relations / Frank Lettke and David M. Klein -- Can't Live With 'Em, Can't Live Without 'Em: Mothers' Ambivalence Toward Their Adult Children / Karl Pillemer -- Intergenerational Ambivalence in the Context of the Larger Social Network / Karen L. Fingerman and Elizabeth Hay -- Intergenerational Ambivalence: Methods, Measures, and Results of the Konstanz Study / Kurt Luscher and Frank Lettke -- The Filial Task in Midlife: Ambivalence and the Quality of Adult Children's Relationships with Their Old-Aged Parents / Frieder R. Lang -- Ambiguous Loss and Ambivalence When a Parent Has Dementia / Pauline Boss and Lori Kaplan -- The Ambivalences of Parental Care Among Young German Adults / Dagmar Lorenz-Meyer -- The Experience of Ambivalence Within the Family: Young Adults "Coming Out" Gay or Lesbian and Their Parents / Bertram J. Cohler -- Ambivalence and Attachment in Family Relationships / Gregory R. Maio, Frank D. Fincham, Camillo Regalia and F. Giorgia Paleari -- The Once and Future Parents: Exploring the Impact of Early Parental Memories on the Anticipated Life Histories of Young Adults / Harry G. Segal.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Parent and adult child; Older people -- Family relationships; Intergenerational relations; Ambivalence; Social theory; Sociology: family & relationships; Social Science -- Sociology -- Marriage & Family